Exploring perceptions of the impact of climate change in three regions in Peru - Torrres-Slimming, Paola Alejandra (2021)
Climate change is directly or indirectly attributed to human activity and is considered the greatest threat to public health of the 21st century. It has impacts on access to water, food, agriculture and livelihoods, and people's health. The objective of this article is to evaluate the perceptions of climate change in children, adolescents, authorities and representatives of youth organizations, women’s organizations and organizations that work with children in the regions of Cusco, Loreto and Piura, in Peru. We conducted a qualitative study using Photovoice with twelve adolescents and in-depth interviews with twenty-two key stakeholders. For the analysis, thematic analysis of the narratives in the photos and of the interviews were used. Extreme changes in weather were identified in all three regions. In the Cusco region they recognized the change in temperature with droughts and frosts, while in Loreto and Piura they showed an increase in rain intensity. In general, these changes affected agriculture. The care of water as a resource, both in its access and quality, was a great concern for all the participants. The study concludes that the concept of climate change as such is not identified, however, they describe changes and variations in the weather that affect their daily activities, particularly agriculture. A cross-cutting theme for all regions was the care and use of the water resource. In addition, young people were particularly enthusiastic about collaborating on future initiatives against climate change.